Analsis Gaya Kepemimpinan dan Budaya Organisasi Terhadap Pengawasan dan Dampaknya Pada Disiplin Pegawai (Jurnal Ekonomi dan Manajemen, 2023)
This research examines the role of disciplinary factors in employee performance, with a focus on leadership style, organizational culture, and supervision. High employee discipline is crucial for ensuring consistent performance, even when there is minimal direct supervision. Leadership style plays a central role in guiding employees to stay aligned with organizational goals and expectations. Meanwhile, organizational culture significantly impacts employee behavior, as it shapes the overall work environment and attitudes towards discipline. Supervision acts as a reinforcing mechanism, ensuring that employees adhere to rules and maintain discipline in the workplace. The study was conducted on employees at the Regional Secretariat of Mojokerto City, with a total population of 110 employees. A sample of 86 respondents was selected using the Slovin formula and simple random sampling method. Data were collected via questionnaires, and responses were analyzed using SPSS Version 22 with path analysis to test the relationships between variables. The findings show that leadership style and organizational culture significantly affect supervision. Leadership style directly influences work discipline, whereas organizational culture does not. However, supervision has a significant positive effect on work discipline, reinforcing the importance of proper oversight. Additionally, leadership style and organizational culture indirectly affect employee discipline through the mediation of supervision. The study concludes that strengthening leadership, fostering a positive organizational culture, and implementing effective supervision mechanisms can improve employee discipline, leading to greater workplace efficiency at the Mojokerto City Regional Secretariat.